George and the new craze - Hemming, Alice; Scott, Kimberley (Minneapolis : Lerner Publications, 2019)
There is a new craze at the wildlife park: People Cards! George the Giraffe and his friends want to collect them all, but they may have to work together to get the full collection!
"The original picture book text for this story has been modified by the author to be an early reader."
Originally published in Horsham, West Sussex by Maverick Arts Publishing Ltd. in 2017.
107888
Keywords: Readers (Primary); Zoo animals -- Juvenile literature; Collectors and collecting; Juvenile fiction